Application of fuzzy cognitive map in simulating strategic information system planning process / Ahmad Fahmi Abu Hassan - Abu Hassan, Ahmad Fahmi (2005)
In this day and age, more researches have been conducted in the domain of Strategic Information System Planning (SISP). However, this is just the continuation from the 1980's where various articles began to probe the underlying causes for the relationship between Information Technology (IT) and businesses. Since then, many academicians and theoreticians have come out with models and approaches to analyze the use of IT from a strategic point of view. Reflect to that, this research is to show the application and capabilities of Fuzzy Cognitive Map (FCM) in simulating SISP business scenarios. This research was conducted because of the level of infancy held by FCM in the SISP domain. Moreover, SISP environment frequently deals with uncertainties and the "whati f circumstances. So, rather than practicing other SISP tools such as Boston Consulting Group (BCG) Matrix, Porter's Five Forces Model and Generic Business Strategies, this research is intended to use FCM as the technique in formulating SISP strategies. In order to achieve the objective, two SISP business scenarios have been designed using FCM technique before being simulated in an open-source simulation program. The simulation program has been developed by its author and using Java programming language. From the simulation, its ou^ut and results have been analyzed and discussed. For the first scenario, it is found that FCM did not provide enough information in decision making for SISP. However, the second scenario showed some promising feature by providing meaningful and interpretable output that can offer broader view for managers in formulating SISP. As recommendations, future researchers should run the simulation on other programs, simulate more SISP scenarios and should also be able to propose a more intricate and extended FCM.